Advanced Magnetohydrodynamics : With Applications to Laboratory and Astrophysical Plasmas - Goedbloed, J. P.; Keppens, Rony; Poedts, Stefaan (Cambridge : Cambridge University Press, 2010)
Following on from the companion volume Principles of Magnetohydrodynamics, this textbook analyzes the applications of plasma physics to thermonuclear fusion and plasma astrophysics from the single viewpoint of MHD. This approach turns out to be ever more powerful when applied to streaming plasmas (the vast majority of visible matter in the Universe), toroidal plasmas (the most promising approach to fusion energy), and nonlinear dynamics (where it all comes together with modern computational techniques and extreme transonic and relativistic plasma flows). The textbook interweaves theory and explicit calculations of waves and instabilities of streaming plasmas in complex magnetic geometries. It is ideally suited to advanced undergraduate and graduate courses in plasma physics and astrophysics.
Title from publisher's bibliographic system (viewed on 09 Oct 2015).
Keywords: Magnetohydrodynamics; Plasma astrophysics